Evaluating long-term outcomes and the impact of small aortic annulus on valve replacement—a novel systematic review and meta-analysis comparing surgery vs. transcatheter interventions - Amin, Aamir; Mohammed, Cara; Kajitani, Sten; AlMashari, Khalid; Kumar, Rajanikant; Sabir, Alifa; Briz-Echeverria, Paulina; Mokhtassi, Shiva; Kallikere Lakshmana, Shashi Kumar; Bokhari, Ahmed; Ehsan, Muhammad; Ahmad, Hasan; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTranscatheter aortic valve implantation (TAVI) is often compared to surgical aortic valve replacement (SAVR) for aortic stenosis treatment. This meta-analysis evaluates the long-term efficacy and safety of TAVI vs. SAVR in aortic stenosis patients, as well as their respective impact on patients with small aortic annulus (SAA).MethodsMEDLINE, Embase, Cochrane Library, and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) and comparative observational studies on TAVI vs. SAVR with long-term follow-up (3–5 years) or SAA. Risk of bias was assessed using the Cochrane Risk of Bias tool (RoB 2.0) and the Newcastle Ottawa Scale. Meta-analyses were conducted with RevMan 5.4 using a random-effects model, with risk ratio (RR) and mean difference (MD) as effect measures.ResultsA total of 17 studies were included in our review. In the long-term analysis, all-cause mortality was significantly higher in the TAVI group [RR 1.10; 95% CI: 1.01–1.19], but the incidence of major bleeding [RR 0.79; 95% CI: 0.68–0.90] and atrial fibrillation was significantly lower [RR 0.37; 95% CI: 0.29–0.48] in the TAVI group. No significant difference was found between the two groups regarding other long-term outcomes. For SAA outcomes, there was no significant difference in terms of all-cause mortality [RR 0.92; 95% CI: 0.63–1.35], although cardiovascular mortality was significantly increased in the TAVI group [RR 2.08; 95% CI: 1.09–3.98]. TAVI significantly increased the rate of major vascular complications [RR 3.58; 95% CI: 1.10–11.61], aortic regurgitation/PVL [RR 6.91; 95% CI: 2.66–17.97], and pacemaker implantation (RR 2.87; 95% CI: 1.74–4.75]. TAVI significantly improved the incidence of prosthesis patient mismatch [RR 0.70; 95% CI: 0.54–0.89], effective orifice valve area (EOA) [MD 0.10; 95% CI: 0.01–0.19], and length of stay in hospital [MD −4.88; 95% CI: −5.52 to −4.23]. There were no significant differences in other clinical or echocardiographic outcomes.ConclusionsTAVI was associated with higher long-term all-cause mortality compared to SAVR in the overall population. Among patients with small aortic annulus, no survival benefit was observed with TAVI, and cardiovascular mortality was significantly increased. Future RCTs should explore SAA-related outcomes with standardized diagnostic criteria.Systematic Review Registrationhttps://www.crd.york.ac.uk, PROSPERO CRD42024541862.